Correlator correspondences for Gaiotto-Rapčák dualities and first order formulation of coset models - Creutzig, Thomas; Hikida, Yasuaki (Journal of High Energy Physics, 2021)
We derive correspondences of correlation functions among dual conformal field theories in two dimensions by developing a “first order formulation” of coset models. We examine several examples, and the most fundamental one may be a conjectural equivalence between a coset (SL(n)k ⊗SL(n)−1)/SL(n)k−1 and sl(n) Toda field theory with generic level k. Among others, we also complete the derivation of higher rank FZZ-duality involving a coset SL(n + 1)k /(SL(n)k ⊗ U(1)), which could be done only for n = 2, 3 in our previous paper. One obstacle in the previous work was our poor understanding of a first order formulation of coset models. In this paper, we establish such a formulation using the BRST formalism. With our better understanding, we successfully derive correlator correspondences of dual models including the examples mentioned above. The dualities may be regarded as conformal field theory realizations of some of the Gaiotto-Rapčák dualities of corner vertex operator algebras.
CRIS-Team Scopus Importer:2024-06-24
Keywords: BRST Quantization; Conformal and W Symmetry; Conformal Field Theory; String Duality